2005
DOI: 10.1186/1471-2148-5-35
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of Wolbachia infections in the fire ant Solenopsis invicta

Abstract: BackgroundWolbachia are endosymbiotic bacteria that commonly infect numerous arthropods. Despite their broad taxonomic distribution, the transmission patterns of these bacteria within and among host species are not well understood. We sequenced a portion of the wsp gene from the Wolbachia genome infecting 138 individuals from eleven geographically distributed native populations of the fire ant Solenopsis invicta. We then compared these wsp sequence data to patterns of mitochondrial DNA (mtDNA) variation of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…We sequenced each PCR amplicon to further verify the PCR products that were amplified from a given PCR assay actually represented the targeted pathogen species. The general methods can be found in Ahrens and Shoemaker (2005). Briefly, PCR amplicons were gel purified, ligated into PCR4-TOPO vector, and transformed into TOP10 competent Escherichia coli cells (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We sequenced each PCR amplicon to further verify the PCR products that were amplified from a given PCR assay actually represented the targeted pathogen species. The general methods can be found in Ahrens and Shoemaker (2005). Briefly, PCR amplicons were gel purified, ligated into PCR4-TOPO vector, and transformed into TOP10 competent Escherichia coli cells (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, other mechanisms such as vertical transmission, loss and reintroduction of infection, populations structure, distinct behaviors and the spreading and radiation of populations [7] may also be important in the phylogenetic grouping we report here for Wolbachia A groups.…”
Section: Discussionmentioning
confidence: 98%
“…We estimated 50% infection rate in the sampled S. invicta mounds which is probably due to Wolbachia-infected and uninfected S. invicta queens invading new areas, generating infected and uninfected nests [7] [8] [24] [25]. A previous study [24], found 10% to 90% prevalence of Wolbachia infection in native populations of S. invicta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations